2003
DOI: 10.1034/j.1399-6576.2003.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Does anaesthesia cause postoperative cognitive dysfunction? A randomised study of regional versus general anaesthesia in 438 elderly patients

Abstract: No significant difference was found in the incidence of cognitive dysfunction 3 months after either general or regional anaesthesia in elderly patients. Thus, there seems to be no causative relationship between general anaesthesia and long-term POCD. Regional anaesthesia may decrease mortality and the incidence of POCD early after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
279
3
37

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(338 citation statements)
references
References 26 publications
9
279
3
37
Order By: Relevance
“…The 17.8% POCD incidence rate found in our study is in the range reported in previous studies as well as the observation that preexisting impaired cognitive function is one of the strongest risk factors for POCD [5][6][7]. Furthermore our study confirms previous reports that POCD may also occur in adult patients at younger ages [1][2][3][4][5].…”
Section: Commentsupporting
confidence: 91%
See 1 more Smart Citation
“…The 17.8% POCD incidence rate found in our study is in the range reported in previous studies as well as the observation that preexisting impaired cognitive function is one of the strongest risk factors for POCD [5][6][7]. Furthermore our study confirms previous reports that POCD may also occur in adult patients at younger ages [1][2][3][4][5].…”
Section: Commentsupporting
confidence: 91%
“…The incidence of postoperative cognitive dysfunction (POCD) varies greatly with reported rates of 4% to 41% after major surgery [5][6][7]. Most POCD cases recover within a few weeks following surgery and anesthesia [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the second study published in 2003 (ISPOD2) found no significant difference in the incidence of cognitive dysfunction 3 months after either general or regional anaesthesia 91. Accordingly, there is no evidence to suggest any causative relationship between general anaesthesia and long‐term POCD.…”
Section: Surgery and Cognitive Dysfunctionmentioning
confidence: 99%
“…14 However, a randomized study of 438 elderly patients compared general vs regional anesthesia and found that the latter decreased the incidence of POCD seven days after major noncardiac surgery. 15 There was no significant difference between S-100ß and NSE levels in patients receiving either anesthetic technique, suggesting that no structural neurologic insult occurred. In a recent study, S-100ß has been shown to increase after major abdominal surgery, while NSE was decreased.…”
Section: Conclusion : Le Premier Jour Après Une Opération Mineure L'mentioning
confidence: 99%